Nutrients Dynamics of Co-composting Poultry Litter with Fast Food Wastes: Co-composting of Poultry Litter with Fast Food Wastes (Biological Sciences - PJSIR, 2015)
Co-composting of poultry litter (PL) and fast food waste (FFW) in different combinations was carried out to explore the nutrient dynamics. The PL and FFW were co-composted in pits of dimensions  2 m×2 m×1.5 m (L×W×D) in ratios of 100:0, 75:25, 50:50, 25:75 and 0:100, respectively, for a period of 105 days. Co-composts of PL and FFW in a 50:50 ratio yielded highest total nitrogen (3.63%), total phosphorus (0.81%), and total potassium (3.40%) levels in the mature compost after 105 days of composting period. Carbon to nitrogen ratio for this combination was 18.33, which is suitable for safe land application. Present study identified PL and FFW co-composting in equal proportions yields maximum N, P and K levels with suitable C:N ratio which may be applied to soils to meet crop nutrient demands and enhanced agricultural productivity.